Gaya Kepemimpinan Kepala Desa dalam Meningkatkan Produktivitas Kinerja Aparatur Desa - Rizka Risdiyanti; Hayat Hayat; Septina Dwi Rahmawati (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The success or failure of the village can be seen from the leadership styles of the village leaders in increasing the productivity of its apparatus. The purpose of this study is to describe and analyze the leadership styles of village leaders in increasing the productivity of village leaders. In this type of qualitative research, the informants in this research are the village leaders and Sawo village officials. This research uses observation and in-depth interviews techniques to collect data. The focus of this research is on the leadership style of village leaders using a transformational leadership style or a transactional leadership style. Based on research findings, we can concluded that there are 2 leadership styles, namely transformational and transactional leadership. The most dominant leadership style used by the head of Sawo village is transformational leadership style. The leaders of Sawo village uses a transformational leadership style. This is proven by the fulfillment of transformational leadership style indicators. The leadership style of the village leaders is able to increase the productivity of the performance of his apparatus. It can be said to be increasing because looking at the performance of the apparatus, the quality and quantity of performance from year to year always increases.